Influência do formato do rebordo alveolar sagital em reabilitações com associação de prótese parcial removível de extremidade livre e implante ósseo integrado - Rezende, Liliana Vicente de Lucas (2011)
The association of mandibular distal extension removable partial dentures with an osteointegrated implant is a treatment option at hasn't been fully explored by modern rehabilitation dentistry yet. The objective of this study is to evaluate, by means of the bidimensional method of finite elements, the distribution of tension on the structures supporting the distal extension removable partial denture (DERPD), associated to a 10.0 x 3.75 mm osteointegrated implant with an ERA retention system, in alveolar ridges of different shapes. Eight models were created, representing, from a sagittal perspective: Model A (MA) – a half arch with a horizontal ridge without posterior support, with the presence of the lower left canine, and a conventional DERPD, with metallic support in the incisal aspect of this canine, as replacement for the first and second pre-molars and the first and second molars of the lower left half arch; Model B (MB) – similar to MA, but different because of the presence of a 3.75 x 10.00 mm implant with an associated ERA retention system in the posterior region of the DERPD base; Model C (MC) - similar to MA, however with a distally ascending ridge format; Model D (MD) – similar to MC, but different because there is an implant associated to a retention system; Model E (ME) - similar to MA, however with a distally descending ridge format; Model F (MF) – similar to ME, but ditfferent in the sense that there is an implant with an associated ERA retention system; Model G (MG) – similar to MA, however with a distally descending-ascending ridge format; Model H (MH) – similar to MG, but different in the sense that there is an implant with an associated ERA retention system. The finite element program ANSYS 9.0 was used to load the models with vertical forces of 50 N, on each cuspid tip. The format of distal descending edge (ME and MF) was that presented worse results, so in the models with conventional RPD as in the models with RPD associated to the implant and ERA system of retention, for the structures gingival mucosa and tooth support. 1) the distally descending ridge presented the most significant stress in the model with the conventional RPD (ME) or with a prosthesis associated to an implant (MF) and 2) the horizontal ridge (MB) provided more relief to the support structures, such as the tooth and the spongy bone, when there was an implant associated to an ERA retention system. The incorporation of the implants with the ERA system retention, in the posterior area of the toothless edge, it promotes larger stability and retention to PPREL, improving the patient's masticatory acting and, consequently, its comfort and function.